Effect of fertility levels and liquid biofertilizers on productivity of Cowpea - Nitu Kumari Saini; Devi Lal Dhaker; O.P. Sharma; Raj Singh Choudhary (Annals of Agricultural Research, 2024)
The field trial was carried out at Research farm of Suresh Gyan Vihar University, Jaipur to evaluate the effect of fertility levels and liquid biofertilizers on productivity of cowpea during kharif season of 2022. The experiment was laid out in factorial randomized block design using four fertility levels (Control, 50% RDF, 75% RDF and 100% RDF) and four liquid biofertilizers (Control, P Fixer, N fixer and N + P fixer) with three replications. The results showed that application of 100% RDFand seed treatment with N + P fixer were well-suited for obtaining higher growth, yield attributes and yields (1519 kg/ha and 1460 kg/ha) of cowpea and it is recommended for higher productivity.